Psychological Distress Among Infertility Patients: A Network Analysis - Cao, Danfeng; Bai, Caifeng; Zhang, Guoxiang (Frontiers in Psychology, 2022)
Background: Psychological distress is common among infertility patients. Total scale scores are often used to represent the severity of anxiety, depression, or stress, which ignores important differences between specific symptoms, and relationships between symptoms. This study aimed to identify patterns of psychological distress experienced by infertility patients, and identify the most central symptoms of anxiety, depression, and stress. Method: From June to September of 2016, 740 infertility patients were included in this cross-sectional study. Infertility patients were asked to complete the Generalized Anxiety Disorder-7, Patients Health Questionnaire-9 (PHQ-9), and Fertility Problem Inventory. Network analysis was used to examine patterns of psychological distress in infertility patients, and test the most central symptoms of anxiety, depression, and stress. Results: Restlessness was the most central symptom in infertility patients. “Feelings of guilt” had the highest strength among PHQ-9 symptoms. “Relationship concern stress” and “sexual concern stress” had the strongest connections in the network. Limitations: The cross-sectional design did not permit identification of causal relationships. Patients in this study were recruited from one reproductive hospital; especially, most patients were ethnic minorities and had low socioeconomic status, which limits generalizability of the findings. Conclusions: This study reinforces the need to better understand the underlying causes of psychological distress in infertile patients. A more detailed investigation of the relationship between these symptoms could provide information for psychosocial interventions aimed beyond “alleviating psychological distress.” We should consider the individual psychological symptom pattern and its potential causes in infertility patients instead of assuming a consistent psychological distress structure.